Effect of Psychological Stress on Some Immunological Parameters Studied in Under Graduate Students - Rojan G. AL-Allaff (Al-Qadisiyah Journal of Pure Science, 2018)
The study deals the immunological effect before and during examination period on twenty undergraduate students with mean age 20(Â±1.7) years of both sexes. We calculating absolute numbers of neutrophils, lymphocytes and monocytes in blood, as well as the estimating of the effectiveness of phagocytic function of neutrophils by using NBT.on other hand serum level of IgG,IgM and C4 were estimated for those individuals. The results showed a significant increase in absolute numbers of monocytes compared with the period before examination  and also a significant reduction in the absolute number of phagocytic cell compared with the period before examination, a significant increase in IgG, C4 serum level compared with the period before examination . The results suggest  that there is a significant differences in some of non specific cellular and humoral  factors and a significant increase in  some of specific  humoral factors in  undergraduate students during examination period.